Critical discussion on ancient language evolution tool to discover world history – Dr. Solehah - Bawazir, Ola; Zakarya, Heba; Yaacob, Solehah@Nik Najah Fadilah (IIUM.fm, 2017)
Insight into Research and Publications is a newly introduced programme of the Research Committee of KIRKHS, aimed at promoting research and publications by the university’s academic community and students. The programme is intended to inspire the audience to conduct research and publications and to learn from others. Assoc. Prof. Dr. Solehah is the second person to be interviewed by IIUM.fm for the programme. She spoke about how Arabic affects human civilisation, people’s thoughts and how it has improved with age and the societies’ evolution. Scholarly studies, she said, have focused on the evolution of Semitic languages and found the group of languages evolved from Akkadian, Aramaic, Phoenician, Hebrew, Arabic, Yemen, Babylonian and Assyrian languages. “There is substantial textual evidence on the existence of ancient Arabic tribes, and the evidence to this reaches far before Islamic times. The lineage of this Ad and Thamud ended with their extinction. The fact that the traces they have left behind are minimal, cannot be used as an indicator for their existence, only being part of local myth and lore.” She added, quoting Surah Al-Najm: 50-51, “It is part of a divine plan, that the Ad and Thamud were to serve as a warning for generations, as stated in the verse, ‘And that He who destroyed the ancient (tribes of) Ad and Thamud, leaving no trace (of them).” Asked about her academic and scientic journey, she responded, “It is challenging and exciting because I deal with dicult and conicting issues associated with history, religion and society.” Nevertheless, she shared her research studies published in many Arabic and English journals and how she criticised some ideas mentioned by the Orientalists. She also found that the Arabic language is the root of Semitic languages and there are many evidences arming this truth.